427. CHARACTERIZATION OF THE CYTOSKELETON-ASSOCIATED PROTEIN 4 (CKAP4) IN A BARRETT'S ESOPHAGUS CELL CULTURE MODEL. (24th September 2022) - Limberger, Beate; Ludwig, Alexandra; Lyros, Orestis; Nowotny, Robert; Gockel, Ines; Thieme, René
Abstract: While the incidence of EAC is rapidly increasing, its prognosis remains poor, with a five-year survival rate of 20%. Consequently, the discovery of new molecular targets for an efficient characterization of EAC patients is necessary. CKAP4 has been attributed to be increased in various cancer entities and has a role in tumorigenesis. However, its role in EAC development and progression is widely unknown. In a Barrett's esophagus, in vitro cell culture model of BE and EAC, CKAP4 expression levels were verified with qPCR, western blot and FACS analysis. In OE33 and OE19 cells a knockdown of CKAP4-expression was done by siRNA for 48 h and 72 h. In siCKAP4 transfected cells FACS (apoptosis), western blot analysis, colony forming assay (CFA), transmigration, adhesion and proliferation assays, were performed. Using western blot, the impact of CKAP4-knockdown on the phosphorylation of Akt, MAP-Kinase, GSK3ß and ß-Catenin was investigated. Furthermore, DKK1-, Ki67- and p21-mRNA-expression was analyzed in siCKAP4 cells using qPCR. CKAP4 was present in all cell lines of the Barrett's sequence (squamous epithelium, metaplasia, dysplasia, and EAC). CKAP4 surface expression was significantly increased in OE33, OE19 and Flo-1 cells. The phosphorylation of Akt was decreased in OE19 cells only, whereas the phosphorylation of MAP-kinase was reduced in OE33 cells, suggesting a role of CKAP4 in tumor-associated proliferation. This was confirmed by decreased colonies in CFA in siCKAP4 cells. FACS analysis showed a significant increase in the amount of apoptotic cells after siCKAP4 transfection. SiCKAP4 led to an increased expression of adhesion molecules, suggesting an impact of CKAP4 in cell adhesion. The role of CKAP4 is barely investigated in EAC at this time. Acting as a Dickkopf-1 (DKK1) receptor, the DKK1-CKAP4-axis might promote cell proliferation independently to the Wnt-pathway. Based on our current results, it can be assumed, that CKAP4 is important for EAC cell growth, proliferation and cell adhesion. Nevertheless, further characterization of CKAP4 is necessary, particularly focusing on the CKAP4-DKK1-axis to provide more evidence for its contribution in EAC development.